Changing channels: Managing channel integration and migration in public organizations - Kernaghan, Kenneth (2013)
The integration and migration of service delivery channels are increasingly important issues for public organizations, involving investment of substantial resources. Designing and implementing a channel integration and migration strategy require attention to: 1) the collection of baseline data on the customers and channels involved with the delivery of each service; 2) an assessment of desirable and feasible changes to the current channel strategy; 3) consideration of the appropriate mix of service channels, with particular reference to incentives to encourage migration to self-service channels; 4) the reduction or removal of barriers to effective channel management and migration. The pursuit of cost savings and improved service, together with the increasing number and upgrading of service channels, will keep channel management high on the service delivery agenda. - Reproduced.
Keywords: Organizations